Allotropic phase transformation and high-temperature tensile deformation behaviour of powder metallurgy Ti-5553 alloy. (August 2020) - Zhao, Qinyang; Yang, Fei; Torrens, Rob; Bolzoni, Leandro
Abstract: Ti-5Al-5V-5Mo-3Cr metastable beta titanium alloy was prepared by rapid thermomechanical powder consolidation approach from blended elemental powder mixture. Allotropic phase transformation and high-temperature tensile behaviour of the consolidated powder metallurgy Ti-5553 alloy were investigated in this work. The studied alloy has a high β phase transformation temperature of 975 °C±5 °C, which is higher than other conventional ingot metallurgy Ti-5553 alloys. The β grains in the microstructure of the alloy are coarsened significantly with increasing the heating temperature from 890 °C to 1050 °C, however, the grain coarsening tendency is mitigated when the heat treatment temperature reach to the range of 1080 °C–1100 °C. The high-temperature tensile mechanical properties of the alloy are sensitive to both the deformation temperature and strain rate, and superplastic deformation of the alloy was achieved at the condition of 850 °C/0.001 s −1 with the tensile elongation of 103.5%. The microstructural evolution characteristics and the fracture mechanisms of the alloy are varied with changing the deformation variables, which are revealed by the microstructure observation of the fractured specimens from different sampling positions. Highlights: Metastable β titanium alloy was prepared by thermomechanical powder consolidation. The PM alloy has a higher β phase transus of 975 °C±5 °C than IM counterparts. Microstructure evolution and fracture mechanisms changes with deformation variables. Superplastic deformation of the alloy is achieved at 850 °C/0.001 s −1 .